Pembuatan Platform WebQGIS sebagai Media Informasi Geospasial Objek dan Fasilitas Umum di Jorong Padang Tarok Nagari Salareh Aia Utara - Windi Nofriani; Eliza (YASIN, 2026)
The use of geospatial information technology has become essential for documenting public objects and facilities and providing structured regional information. However, information on public objects and facilities in Jorong Padang Tarok, Salareh Aia Utara Nagari, has not yet been comprehensively documented in a digital map presenting the location and attributes of each object. This activity aimed to develop a WebQGIS platform as a medium for providing geospatial information on public objects and facilities in Jorong Padang Tarok. This activity employed a descriptive approach using a geospatial information product development method. Data on public objects and facilities were obtained from the Government of Salareh Aia Utara Nagari and subsequently processed using QGIS based on geographic latitude and longitude coordinates. Spatial descriptive analysis was conducted through object inventory, category classification, point-layer creation, attribute assignment, map visualization, and publication of the results in WebQGIS format. The results showed that nine object locations were successfully mapped, comprising three prayer rooms, two futsal courts, one jorong office, one school, one community health center/animal health center facility, and one tourist attraction. This processing produced spatial data, a digital map, and a WebQGIS platform containing location information and the attributes of each object. This activity provides an initial geospatial information database for Jorong Padang Tarok that can be further developed to support more integrated regional documentation and information presentation. Future development should expand the range of objects, complete the information attributes, verify the data, and conduct platform dissemination, testing, and usage evaluation.